Tear Production Rate in a Mouse Model of Dry Eye According to the Phenol Red Thread and Endodontic Absorbent Paper Point Tear Tests - Kilic, Servet; Kulualp, Kadri (Amer Assoc Laboratory Animal Science, 2016)
This study compared the endodontic absorbent paper point test (EAPTT) and the phenol red thread test (PRTT) for the assessment of tear production rate in a mouse model of dry eye. Fourteen BALB/c breed female mice were allocated into experimental and control groups of equal number. For 6 wk, the experimental group was kept in dry-eye cabinets, whereas the control group was kept in normal cages under ambient conditions. In both groups, the tear production rate was measured by using EAPTT and PRTT before the study, at study baseline, and at weeks 2, 4, and 6. Tear production at weeks 2, 4, and 6 differed significantly between groups and tests. Evaluating the groups independently in terms of the test technique revealed significant differences in teat production rate between the 2 groups at the same measurement times. Due to their persistent exposure to evaporative stress factors, the tear production rate of the mice in the dry-eye cabinet was consistently lower than that of controls. Unlike PRTT, EAPTT can be readily applied to the small globes of laboratory animals without the need for forceps, thus saving time and effort. In addition, EAPTT was practical and imposed no undue stress on the mice, due to the test material's firmer structure. Therefore, compared with PRTT, EAPTT is safer and more reliable for the diagnosis of dry-eye syndrome in mice.
Keywords: Ocular Surface; Keratoconjunctivitis Sicca; Animal-Models; Murine Model; Mice; Limitations; Stress; Rabbit; Agents; Gland